Mutual fund performance: a case study of Malaysia equity-based fund (2001 - 2005) / Lena Muhiden - Muhiden, Lena (2007)
This study aims to evaluate the performance of Malaysia equity-based mutual funds over a five years period (1/1/2001 - 31/12/2005). Specifically, the study focuses on sixteen equity-based funds with relates to the relationship between fund performance with current return, management expense ratio and manager experience. The Pearson Correlation Coefficient and Simple Linear Regression Analysis are used to evaluate the performance of the equity-based mutual fund. The conclusion of this study is that none of the sixteen funds shows a positive statistical significant coefficient between current return and fund performance. Besides, only one fund showed a significant relationship between management expense ratio and fund performance. Apart from this, five funds showed a positive significant relationship between manager experience and fund performance. Hence, a longer manager experience does add value to a fund but does not ensure a persistence higher return. Thus, in overall this means that an increase in these variables; current return, management expense ratio and manager experience would not have any strong effect on fund performance.